2021
DOI: 10.2106/jbjs.21.00176
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Sleep Disturbances to Orthopaedic Surgery

Abstract: Sleep disturbances can increase the risk of falls and motor vehicle accidents and may reduce bone density.Poor sleep can lead to worse outcomes after fracture, such as chronic pain and delayed recovery.Orthopaedic surgeons can play an important role in the screening of sleep disorders among their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…According to a meta-analysis, sleep disturbances were found to have a significant correlation with chronic postsurgical pain [ 9 ]. Another investigation revealed that sleep disorders might enhance the likelihood of falls and reduce bone density [ 10 ]. Numerous other studies have demonstrated that perioperative sleep disturbances have a detrimental impact on both short-term and long-term patient outcomes [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a meta-analysis, sleep disturbances were found to have a significant correlation with chronic postsurgical pain [ 9 ]. Another investigation revealed that sleep disorders might enhance the likelihood of falls and reduce bone density [ 10 ]. Numerous other studies have demonstrated that perioperative sleep disturbances have a detrimental impact on both short-term and long-term patient outcomes [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pain can lead to cardiovascular, neuroendocrine, gastrointestinal, and other system abnormalities. In addition, it also triggers emotional symptoms like the anxiety and insomnia, which can even aggravate the development of the disease and affect the postoperative recovery [7–9] . Therefore, how to alleviate the pain, adverse emotions and psychological pressure, as well as improve the sleep quality is of significance to achieve a good outcome in postoperative orthopedic patients.…”
Section: Introductionmentioning
confidence: 99%